Total Devotion: Dismantling Religious Practices and Training Devotion in 2 Kings 22-23 - Feldt, Laura (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2020)
The demise and disappearance of religions are processes rarely analysed or theorised in depth in the study of religions. This article engages the discussion of how religious traditions disappear by focusing on religious demise as an active process and suggests that this can also teach us about religious persistence. Using memory and emotion perspectives, I focus on processes of religious change in Judaism in the Persian-Hellenistic era by analysing a case study from the Hebrew Bible that involves an active dismantling of previous religious practices and their replacement with a new programme for religious devotion: the narrative of 2 Kgs 22-23. I argue that the new total devotion programme involves the active erasure of previous religious practices as a key part of the new identity. On the basis of the analyses, I discuss religious changes in Second Temple Judaism and suggest a novel reframing of some of the key changes in terms of memory, media, and emotions.